Analyzing the Impact of VMBR Training on Table Tennis Players’ Competence in Performing Alternate Counter and Forehand Drive Shots With Precision - Sharma, Arnav; Prasad, Brij Kishore; Das, Rajdeep; Sharma, Ashish; Karmakar, Debajit; Choudhary, Prashant Kumar (Physical Education Theory and Methodology, 2024)
Objectives. The study aimed to examine the impact of VMBR training on performing certain table tennis skills. Materials and methods. A total of 50 male state table tennis players, aged between 17 and 23, were selected at the Inspire Table-Tennis Academy in Secunderabad, Telangana. These players were randomly divided into two groups: an experimental group and a control group, each comprising 25 participants. The experimental group underwent a 12-week VMBR training regimen three times a week, while the control group simply continued with their regular daily practice routines. Prior to the study and after the 12-week period, assessments were conducted using Pushpendra Purashwani’s table tennis skill tests, specifically the alternate counter test and the forehand drive techniques on target test, developed in 2011. Statistical analyses involved the application of dependent t-tests and descriptive statistics to evaluate the outcomes. Results. The experimental group’s results indicated that both the alternate counter test and the forehand drive on target test had a marked positive effect on players of table tennis at the 0.01 significance level. The study contributes to our understanding of psychological elements’ crucial role in influencing skill performance. Conclusions. The research delves into how various psychological factors affect performance. Previous studies have demonstrated that visualization and images can significantly enhance performance. Table tennis players can overcome mental hurdles through a systematic psychological technique called rehearsal. This process involves mentally replaying an event in a step-by-step manner. The phases of Visual Motor Behavior Rehearsal (VMBR) that lead to better performance include technique refinement, error analysis and correction, preparation for competition, and enhancement of psychological aspects. Future studies could investigate VMBR’s impact on specific table tennis skills or other sports in order to assist athletes in improving their psychological parameters and performance.